2009
DOI: 10.1142/s0217979209049917
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL PROPERTIES OF CHEMICALLY PREPARED CdS QUANTUM DOTS IN POLYVINYL ALCOHOL

Abstract: Excitonic effects are observed in the optical absorption and photoluminescence of strongly confined CdS quantum dots embedded in the polymer matrix. CdS nanoparticles of different crystallite sizes have been prepared by chemical route with polymer as a host material. The CdS nanocomposite film was made up of particle smaller than 5 nm and shows a composite band gap up to 3.2 eV, whereas the band gap for bulk hexagonal CdS is about 2.42 eV. Photoluminescence spectra show a strong emission band corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It was found that the Stokes shifts of PVA and PVA–ZnS composites are 151 and 185.5–196 nm, respectively. Similar larger Stokes shift of the PVA and PVA-based materials were observed and explained in ref (33). Furthermore, looking at the PL spectra, it can be seen that the intensity increases for all composite samples compared to PVA (Figure 4).…”
Section: Results and Discussionsupporting
confidence: 88%
“…It was found that the Stokes shifts of PVA and PVA–ZnS composites are 151 and 185.5–196 nm, respectively. Similar larger Stokes shift of the PVA and PVA-based materials were observed and explained in ref (33). Furthermore, looking at the PL spectra, it can be seen that the intensity increases for all composite samples compared to PVA (Figure 4).…”
Section: Results and Discussionsupporting
confidence: 88%
“…Factors such as control of film thickness and deposition rate by varying the solution pH, temperature and reagent concentration are allied with the ability of CBD to coat large areas in a reproducible and low cost process. Another advantage of CBD method with respect to other methods is that the films can be deposited on different kinds, shapes and sizes of substrates (Kale and Lokhande 2005;Barman et al 2008).…”
Section: Study Of CD (1−x)mentioning
confidence: 99%
“…The shifting of peak position to higher diffraction angle due to strain was confirmed by calibrating the XRD prior to each observation using standard silicon sample. 11,12 The size of the nanocrystal was determined using Scherer formula 13…”
Section: Tem Observationmentioning
confidence: 99%